Better, Not Just More—Contrast in Qualitative Aspects of Reward Facilitates Impulse Control in Pigs - Zebunke, Manuela; Kreiser, Maren; Melzer, Nina; Langbein, Jan; Puppe, Birger (Frontiers in Psychology, 2018)
Delay-of-gratification paradigms, such as the famous ‘Marshmallow Test’, are designed to investigate the complex cognitive concepts of self-control and impulse control in humans and animals. Such tests determine whether a subject will demonstrate impulse control by choosing a large, delayed reward over an immediate, but smaller reward. Documented relationships between impulsive behavior and aggression in humans and animals suggest important implications for farm animal husbandry and welfare, especially in terms of inadequate social behavior, tail biting and maternal behavior. In a preliminary study, we investigated whether the extent of impulse control would differ between quantitatively and qualitatively different aspects of reward in pigs. Twenty female piglets were randomly divided into two groups, with ten piglets each. After a preference test to determine individual reward preference among six different food items, a discrimination test was conducted to train for successful discrimination between different amounts of reward (one piece vs. four pieces) and different qualitative aspects of reward (highly preferred vs. least preferred food item). Then, an increasing delay (2 s, 4 s, 8 s, 16 s, 24 s, 32 s) was introduced for the larger/highly preferred reward. Each piglet could choose to get the smaller/least preferred reward immediately or to wait for the larger/highly preferred reward. Piglets showed clear differences in their preference for food items. Moreover, the “quality group” displayed faster learning in the discrimination test (number of sessions until 90 % of the animals completed the discrimination test: “quality group” - three days vs. “quantity group” - five days) and reached a higher level of impulse control in the delay-of-gratification test compared to the “quantity group” (maximum delay that was mastered: “quality group” - 24 s vs. “quantity group” - 8 s). These results demonstrate that impulse control is present in piglets but that the opportunity to get a highly preferred reward is more valued than the opportunity to get more of a given reward. This outcome also underlines the crucial role of motivation in cognitive test paradigms. Further investigations will examine whether impulse control is related to traits that are relevant to animal husbandry and welfare.